2005
DOI: 10.1016/j.molcel.2005.02.023
|View full text |Cite
|
Sign up to set email alerts
|

Defining a Centromere-like Element in Bacillus subtilis by Identifying the Binding Sites for the Chromosome-Anchoring Protein RacA

Abstract: Chromosome segregation during sporulation in Bacillus subtilis involves the anchoring of sister chromosomes to opposite ends of the cell. Anchoring is mediated by RacA, which acts as a bridge between a centromere-like element in the vicinity of the origin of replication and the cell pole. To define this element we mapped RacA binding sites by performing chromatin immunoprecipitation in conjunction with gene microarray analysis. RacA preferentially bound to 25 regions spread over 612 kb across the origin portio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
90
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(92 citation statements)
references
References 49 publications
2
90
0
Order By: Relevance
“…During sporulation in Bacillus subtilis, for example, the RacA and DivIVA proteins combine to anchor the chromosomal origin region to the cell pole (41). RacA binds to 25 sites spread over a 612-kb region of originproximal DNA (42), and DivIVA (which does not share sequence similarity with PopZ) is required for RacA-mediated localization of this region to the pole (41). The Escherichia coli chromosome, in turn, does not contain a parABS locus, but it has been shown that the migS cis-acting sequence affects bipolar localization of the origin region in this species (43).…”
Section: Discussionmentioning
confidence: 99%
“…During sporulation in Bacillus subtilis, for example, the RacA and DivIVA proteins combine to anchor the chromosomal origin region to the cell pole (41). RacA binds to 25 sites spread over a 612-kb region of originproximal DNA (42), and DivIVA (which does not share sequence similarity with PopZ) is required for RacA-mediated localization of this region to the pole (41). The Escherichia coli chromosome, in turn, does not contain a parABS locus, but it has been shown that the migS cis-acting sequence affects bipolar localization of the origin region in this species (43).…”
Section: Discussionmentioning
confidence: 99%
“…Alternative mechanisms may involve forespore-specific DNA-protein complexes that could obstruct DNA translocation by the forespore SpoIIIE exporter by creating DNA roadblocks or membrane anchors. These complexes could include the ParB homolog Spo0J, which compacts the originproximal region into filamentous protein-DNA architectures 1,39,40 , and RacA, which tightly tethers the chromosomal origin to the cell pole [40][41][42] . The late appearance of translocation reversal events could be related to the release of oriC tethering later in the process of sporulation.…”
Section: Discussionmentioning
confidence: 99%
“…Other bacteria have more complex segregation scenarios: B. subtilis and Caulobacter crescentus use asymmetric septum formation in differentiation, initiating endospores in the former and in the latter generating swarmer and stalked cells with different developmental prospects. These two bacteria have a centromere-like element represented by sequences extending for several hundred base pairs around oriC, together with proteinsRacA in B. subtilis and MreB in C. crescentusthat bind to it and help anchor chromosome copies to the cell poles (11,12,35).…”
Section: Chromosome Movement During Colony Growth and Developmentmentioning
confidence: 99%